"Was It Good for You?": Recasting Catholic Sexual Ethics in Light of Women's Sexual Pain Disorders. Issue 4 (30th November 2018) - Antus, Elizabeth L.
Abstract: Over the past one hundred years, Catholic sexual ethics has become more hospitable to sexual bonding as a good that is distinct from procreation. However, our increasing knowledge of women's sexual pain disorders highlights ongoing problems with official Catholic sexual ethics. This essay argues that the Catholic Church still reproduces gendered social scripts that unwittingly encourage heterosexual women to ignore their sexual pain and continue to engage desperately in intercourse, out of an exacerbated concern to satisfy male partners. These are tactics that only prolong and deepen women's sexual suffering. Further, insights about the various options for women's healing from sexual pain concretely suggest more liberative sexual scripts: the importance of women's non‐obligatory, embodied desire and the need to reject intercourse as the compulsory norm for all sexual activity. Ultimately, women's experiences of having sexual pain and healing from it lead to revisions in Catholic sexual ethics at a fundamental level.